2020
DOI: 10.1002/asia.202000111
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Mode Microwave Heating‐Induced Concurrent Out‐of‐Plane Twin Growth Suppression and In‐Plane Epitaxial Growth Promotion of b‐Oriented MFI Film under Mild Reaction Conditions

Abstract: In this study, single-mode microwave heating was applied in epitaxial growth of b-oriented MFI seed monolayer prepared by facile manual assembly, resulting in the formation of well-intergrown and highly b-oriented MFI film with few twins. It exhibited a precise molecular sieving property at a reaction temperature no higher than 100°C within 2 hours, therefore making it possible for easy operation in an open environment. The capability for concurrent suppression of undesired out-of-plane twin growth and promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Previous research indicated that relying on the unique thermal and non‐thermal effects of microwave irradiation, microwave‐assisted synthesis of zeolite membranes enabled not only a significant reduction in reaction time but also a decrease of intercrystalline defect density in comparison with conventional heating, which was quite advantageous for the production of large membrane areas [14] . Moreover, our recent study implied that single‐mode microwave heating exhibited obvious superiority over common multi‐mode microwave heating in terms of microwave field uniformity and intensity, resulting in concurrent reduction in the reaction temperature and time required for the formation of well‐intergrown MFI zeolite membranes [7, 15] . Indeed, our experimental results indicated that well‐intergrown MFI zeolite (denoted as H‐MFI) membrane could be obtained at 105 °C within 2 h (Figure 2 g).…”
Section: Figurementioning
confidence: 66%
See 1 more Smart Citation
“…Previous research indicated that relying on the unique thermal and non‐thermal effects of microwave irradiation, microwave‐assisted synthesis of zeolite membranes enabled not only a significant reduction in reaction time but also a decrease of intercrystalline defect density in comparison with conventional heating, which was quite advantageous for the production of large membrane areas [14] . Moreover, our recent study implied that single‐mode microwave heating exhibited obvious superiority over common multi‐mode microwave heating in terms of microwave field uniformity and intensity, resulting in concurrent reduction in the reaction temperature and time required for the formation of well‐intergrown MFI zeolite membranes [7, 15] . Indeed, our experimental results indicated that well‐intergrown MFI zeolite (denoted as H‐MFI) membrane could be obtained at 105 °C within 2 h (Figure 2 g).…”
Section: Figurementioning
confidence: 66%
“…[14] Moreover, our recent study implied that single-mode microwave heating exhibited obvious superiority over common multi-mode microwave heating in terms of microwave field uniformity and intensity, resulting in concurrent reduction in the reaction temperature and time required for the formation of wellintergrown MFI zeolite membranes. [7,15] Indeed, our experimental results indicated that well-intergrown MFI zeolite (denoted as H-MFI) membrane could be obtained at 105 8C within 2 h (Figure 2 g). The cross-sectional SEM image (Figure 2 h) clearly showed that prepared membrane was composed of an ultra-thin (ca.…”
Section: Angewandte Chemiementioning
confidence: 78%
“…Zeolite membranes have received extensive attention for energy efficient separation, owing to their well-defined pore structure, robust framework, and excellent stability. Previous studies confirmed that the microstructure of zeolite membranes, including preferred orientation, membrane thickness, and grain boundary structure, exerted significant influence on their separation performance. , For instance, the superior performance of b -oriented MFI zeolite membranes has been demonstrated for isomer separation (e.g., n -/ i -butane and p -/ o -xylene), while defect-free ultrathin zeolite membranes commonly exhibited superior gas separation performance. , It should be noted that, in spite of significant progress on microstructure optimization and performance enhancement of zeolite membranes, under most circumstances, zeolite membrane growth has to be performed at relatively high temperature (commonly >100 °C), which inevitably leads to increased capital investment, operating cost, and energy consumption; simultaneously, safety concerns have to be taken into consideration under autogenous pressure. …”
mentioning
confidence: 99%
“…Recently, significant efforts have been devoted to reducing the reaction temperature of zeolite membranes. Diverse approaches, e.g., reactive growth, flux synthesis, and microwave heating ,, have been developed for mild synthesis of zeolite membranes. However, room temperature (RT) synthesis of continuous zeolite membranes, which is advantageous in terms of economic and environmental benefits, remains a great challenge.…”
mentioning
confidence: 99%
See 1 more Smart Citation